1997
DOI: 10.7751/telopea19971001
|View full text |Cite
|
Sign up to set email alerts
|

Notes on Vallisneria (Hydrocharitaceae) in Australia, with descriptions of two new species

Abstract: descriptions of two new species. Telopea 7(2): 111-118. Five species of Vallisneria are recognised from Australia, namely the cauline-leafed species V. caulescens and V. triptera and the non-cauline or tufted species V. americana (var. americana), V. nana and V. annua. Two of these, Vallisneria triptera and Vallisneria annua, are described here as new species from northern Australia, and an earlier name, Vallisneria nana R. Br., reinstated for a common Australian species. V. gracilis Bailey is recognised as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Originally I planned to work with Surrey on Zostera during my sabbatical visit to Australia in 1999-2000, but he had other thoughts. His interest in Vallisneria was first whetted by the discovery of two new species (Jacobs & Frank 1997). Soon afterwards he wrote a popular account of the Australian Vallisneria species for the aquarist journal Aqua-Planta (Jacobs 1999a(Jacobs , 1999b, which reinforced his 'outreach' commitment to disseminate the practical applications of his taxonomic research.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Originally I planned to work with Surrey on Zostera during my sabbatical visit to Australia in 1999-2000, but he had other thoughts. His interest in Vallisneria was first whetted by the discovery of two new species (Jacobs & Frank 1997). Soon afterwards he wrote a popular account of the Australian Vallisneria species for the aquarist journal Aqua-Planta (Jacobs 1999a(Jacobs , 1999b, which reinforced his 'outreach' commitment to disseminate the practical applications of his taxonomic research.…”
Section: Introductionmentioning
confidence: 99%
“…His interest in Vallisneria was first whetted by the discovery of two new species (Jacobs & Frank 1997). Soon afterwards he wrote a popular account of the Australian Vallisneria species for the aquarist journal Aqua-Planta (Jacobs 1999a(Jacobs , 1999b, which reinforced his 'outreach' commitment to disseminate the practical applications of his taxonomic research. So, soon after Surrey first picked me up to begin our Zostera field work, he stopped to point out a stand of Vallisneria, indicating that the Australian botanists had been calling it V. americana.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigators have demonstrated that aquatic macrophytes play a major role in nutrient cycling of many freshwater systems (Ozimek et al 1990;Wigand et al 1997;Morris et al 2003;Huss and Wehr 2004). The genus Vallisneria includes approximately ten species, with Vallisneria gigantea Graebner found in Australia, New Zealand, Malaysia and some parts of the USA (Jacobs and Frank 1997). This species is known to be sensitive to irradiation and inorganic carbon conditions (Korschgen et al 1997;Wigand et al 1997).…”
Section: Introductionmentioning
confidence: 99%